2015
DOI: 10.1080/15533174.2013.862661
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear Manganese(II)/4′-Ar-2,2′:6′,2″–Terpyridine Complexes: Synthesis, Characterization, and Olefins Oxidation Study

Abstract: A series of mononuclear Mn(II)/terpyridine complexes were synthesized and characterized by elemental analysis, IR spectrum, and UV-vis spectrum. Catalytic activities of Mn(II)/4 0 -Ar-2,2 0 :6 0 ,2 00 -terpyridine complexes were tested in the oxidation of cyclohexene or styrene in the presence of tert-butylhydroperoxide as oxidant. Significant catalytic effects of these complexes were observed in the oxidation of olefins, especially in the cyclo-oxidation of styrene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This study not only contributes to the understanding of manganese-based catalysis but also highlights the potential utility of these manganese complexes, specically 4 0 -Ar 2,2 0 :6 0 ,2 00 -TPY ligated manganese(II) complexes, in the development of efficient and selective catalytic systems for olen oxidation and cycloaddition reactions, with a particular emphasis on their application in the oxidation of styrene using tert-butylhydroperoxide as an oxidant. 64 The results revealed that the products of cyclohexene 114 were 2-cyclohexene-1-one 115, 2-cyclohexene-1-ol 116, and cyclohexene epoxide 117. 64 Effects of different Mn(II) for conversion of cyclohexene oxidation are shown in Table 6.…”
Section: Catalysismentioning
confidence: 99%
See 3 more Smart Citations
“…This study not only contributes to the understanding of manganese-based catalysis but also highlights the potential utility of these manganese complexes, specically 4 0 -Ar 2,2 0 :6 0 ,2 00 -TPY ligated manganese(II) complexes, in the development of efficient and selective catalytic systems for olen oxidation and cycloaddition reactions, with a particular emphasis on their application in the oxidation of styrene using tert-butylhydroperoxide as an oxidant. 64 The results revealed that the products of cyclohexene 114 were 2-cyclohexene-1-one 115, 2-cyclohexene-1-ol 116, and cyclohexene epoxide 117. 64 Effects of different Mn(II) for conversion of cyclohexene oxidation are shown in Table 6.…”
Section: Catalysismentioning
confidence: 99%
“…This study not only contributes to the understanding of manganese-based catalysis but also highlights the potential utility of these manganese complexes, specifically 4′-Ar 2,2′:6′,2′′-TPY ligated manganese( ii ) complexes, in the development of efficient and selective catalytic systems for olefin oxidation and cycloaddition reactions, with a particular emphasis on their application in the oxidation of styrene using tert -butylhydroperoxide as an oxidant. 64 …”
Section: Applications Of Terpyridine-based Metal Complexesmentioning
confidence: 99%
See 2 more Smart Citations